Mucosal vulval lichen planus: outcome, clinical and laboratory features. - Kirtschig, G; Wakelin, S; Wojnarowska, F (2005)
BACKGROUND: Mucosal lichen planus of the vulva is a rare but increasingly recognized condition. It has potentially severe complications such as fusion of the labia and vagina; the risk of developing squamous cell carcinoma (SCC) may be increased. An association between hepatitis B and C infection and skin or oral lichen planus appears to exist in certain geographical areas. OBJECTIVE: To investigate the course of mucosal vulval lichen planus, its response to treatment and associated laboratory features. SUBJECTS AND METHODS: Forty-four women with mucosal vulval lichen planus were studied between 1997 and 2000 and laboratory data were collected. RESULTS: Thirty of 44 patients had additional oral lesions, only nine had cutaneous findings compatible with lichen planus. We did not find an association with antibodies to hepatitis B or C virus in this British study population. All women were treated with potent to very potent topical corticosteroids; however, in the majority of patients symptoms persisted. In seven (16%) patients vulval lichen planus was in remission after a disease duration between 2 and 18 years (mean 10.6 years). One patient developed a vulval SCC. CONCLUSIONS: Screening for hepatitis B and C in women with mucosal vulval lichen planus in the UK seems unnecessary. We recommend long-term follow-up, and that all non-healing ulcerative and papular lesions should be biopsied.